Exploratory research on the effects of repetitive transcranial magnetic stimulation (rTMS) on musculoskeletal biomarkers on stroke patients in Hospital Universiti Sains Malaysia - Balakrishnan, Sri Ratha (2019)
The leading cause of long-term disability caused by stroke is motor impairment. Neuroplasticity-induced cortical reorganization is a crucial process mediating motor recovery following stroke. Repetitive transcranial magnetic stimulation (rTMS) is a form of non-invasive brain stimulation approach that promotes neuroplasticity by modulating cortical excitability. We tested the effects of rTMS, when delivered over the ipsilesional hemisphere at the site of primary motor cortex (M1). Previous studies have reported elevated levels of serum Creatine Kinase (CK) and Troponin T among individuals with stroke. These serum enzymes are widely used as biomarkers for functional status of skeletal muscles. The aim of the present study is to assess the changes in the CK and Troponin T levels in response to 10 Hz rTMS in individuals with ischemic and hemorrhagic stroke. Eight stroke patients were screened according to inclusion and exclusion criteria. Subsequently, they were subjected to 10 sessions of fascilitatory protocol of rTMS on the ipsilesional hemisphere for a period of two weeks. The blood samples of the patients were obtained pre- and post-intervention in order to analyze the levels of CK and Troponin T. Statistical analysis revealed that there is no statistically significant difference in the median values of CK and Troponin T pre- and post-rTMS. Descriptive analysis indicated that the median values of CK and Troponin T at the baseline are higher than post-rTMS in this sample. In addition, stroke patients in the older age group were found to have higher levels of CK and Troponin T as compared to the younger patients. The considerable interindividual variability in CK and Troponin T activities among stroke patients can be ascribed to several confounding variables and relatively small sample size. Therefore, it can be suggested that future studies may include factors such as physical activity status, medical history of patients and types of medications in the analysis in order to assess the serum levels of aforementioned biomarkers, as a reliable indicator of muscle cells integrity following rTMS.